UPAYA MENINGKATKAN HASIL BELAJAR PADA MATERI KITAB-KITAB ALLAH DENGAN PENGGUNAAN MODEL PEMBELAJARAN TALKING STICK DI KELAS V SDN 27 BILAH HULU - Halimatussahdiyah Halimatussahdiyah (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This research aims (1) to find out how learning is implemented using the Talking Stick learning model in Islamic Religious Education Subjects, Material on the Books of Allah in class V at SDN 27 Bilah Hulu (2) To find out whether the application of the Talking Stick learning model can improve learning outcomes in the Islamic Religious Education Subject Material on the Books of Allah in class V at SDN 27 Bilah Hulu. This research is of the type Classroom Action Research (PTK). The subjects in this research were Class V of SD Negeri 6 Bilah Hulu, totaling 27 people consisting of 15 boys and 12 girls, while the object of this research was the application of the talking stick learning model in Class V of SDN 27 Bilah Hulu for the 2021 Academic Year/ 2022. Based on the results of data analysis and discussion throughout the research stage, the researcher concluded that implementing learning using the Talking Stick learning model can improve PAI (Islamic Religious Education) Learning Outcomes on the Books of Allah as well as being able to increase teacher abilities and student activities at SDN 27 Bilah Hulu. In the initial test, student learning completion was 51.85% and increased to 70.37%, which means an increase of 18.52%. The increase in learning completeness in cycle II increased by 14.82%, namely in cycle I 70.37% to 85.19% in cycle II. The average student ability also increased, in the initial test the average student ability increased from 52.22% to 63.70%, meaning an increase of 11.48%. In cycle II, the average student ability increased by 20.00%, namely from 63.70% to 83.70%. The results of teacher observations in managing learning increased by 19.23% (in cycle I 67.31% increased to 86.54% in cycle II), while the increase in observations of student activities increased by 25.00% (in cycle I 60.71 % increased to 85.71% in cycle II).